ISLAMIC EDUCATIONAL VALUES IN HADITS AQIQAH - Nur Arifuddin; Moh Zahiq; Ali Mustofa; Nurkhamimi Zainuddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Islamic education aims to develop students not only physically but also spiritually.Education is not only done in school, but also from observations, from the Qur'an or Hadith, one of the hadiths containing Islamic education is the hadith about aqiqah: The hadith of aqiqah is one of the education of children during childhood. Seeing the situation and conditions of society that deviate among teenagers, which is caused by the lack of parental attention to children's education during childhood. So this study focuses on. how are the values ??of Islamic education, and how are the values ??of Islamic education in the hadith of aqiqah. This study is a type of Library Research or literature review research, namely research that critically and deeply examines library materials as a source of ideas. The research approach used is a descriptive analysis approach. Aqiqah worship is one thing that contains Islamic educational values ??that we can take in order to deliver and educate children to become pious Muslims. One of the educations given by parents to children is educating children since they are born by applying Islamic educational values ??that are relevant to children's education. Among the educations that parents can give to newborn children is to perform the aqiqah on the seventh day, if not, on the fourteenth day. If not, then on the second day. Because aqiqah contains Islamic educational values ??that are useful for equipping children to have good morals according to the hopes of their parents. Among the values ??contained in aqiqah are faith education, moral education, and health education.